Conservative Management of Spontaneous Isolated Dissection of the Superior Mesenteric Artery - Jae Hyun Kwon; Yoon Hee Han; Jun Kyu Lee (Gastroenterology Research and Practice)
Purpose. We report the clinical outcomes of patients with spontaneous isolated dissection of the superior mesenteric artery (SIDSMA) who were treated conservatively. Materials and Methods. A retrospective review was performed in 14 patients from 2006 to 2016 with SIDSMA. Their clinical features and computed tomographic angiography (CTA) characteristics, treatment methods, and clinical outcomes were analyzed. The mean age was 53.6 (range, 41–73) years, and the mean follow-up duration was 20.6 (range, 1–54) months. Conservative management was the primary treatment if no bowel ischemia or arterial rupture was noted. Results. The mean initial abdominal visual analog pain score was 7 (range, 5–9) in seven patients. The mean total duration of abdominal pain was 10.2 days (range, 2–42 days) in 10 patients. The mean percentage stenosis of the dissected SMA at the initial presentation was 78.8% in 14 patients. Complete obstruction of the SMA at the initial presentation was evident in 4 of the 14 patients (28.6%). Conservative management was successful in all 14 patients. None of the 14 patients developed bowel ischemia or an infarction. Abdominal pain did not recur in any patient during follow-up (mean, 20.6 months; range, 1–54 months). Conclusion. Conservative management was successful for all SIDSMA patients, even those with severe compression of the true lumen or complete obstruction of the dissected SMA.